Dasaparami Appeared in Thai Literature Titled Phra Aphai Mani - Supha, Aphidej (วารสารมนุษยศาสตร์ มหาวิทยาลัยมหามกุฏราชวิทยาลัย, 2021)
The purpose of this article is to present the Dhamma principles of Dasaparami appearing in Thai literature titled Phra Aphai Mani. According to Buddhist teachings, it is very important to the way of life of Thai people and Thai society. The practice of dharma consists of a cause, know and understand the truth. It will also be a tool for improving the lives of those who are interested in doctrinal principles. Learning the principles of Buddhist teachings will appear both Buddhist literature and Thai literature. For Thai literature, Phra Aphai Manee is the best and most complete work of Sunthorn Phu. both in terms of content, language idioms, and morals. can learn and easy to understand Suitable for those who are interested.